INTEGRASI NILAI-NILAI MODERASI BERAGAMA DALAM PENDIDIKAN ISLAM: PERSPEKTIF LITERASI AKADEMIK - Yusuf Anggia, Iqbal (HASBUNA : Jurnal Pendidikan Islam, 2025)
Religious moderation emphasizes balance in practicing religion to foster social harmony amidst diversity. In the context of Islamic education, integrating the values of religious moderation is crucial to shaping a generation with inclusive, tolerant, and adaptive attitudes toward differences. This study aims to analyze the integration of religious moderation values in Islamic education from the perspective of academic literacy. Employing a qualitative approach and a literature review method, the research examines various relevant sources, including journals, books, and academic documents. The findings indicate that religious moderation values can be integrated through value-based curricula, interactive learning emphasizing discussions, and the habituation of inclusive religious practices within educational settings. Academic literacy serves as a vital framework for critically and analytically understanding and conveying these values. Moreover, enhancing students' academic literacy supports their internalization of religious moderation values in thought and daily behavior